The role of family meal frequency in common mental disorders in children and adolescents over eight months of follow-up - Agathão, Beatriz Tosé (PLoS One, 2021)
OBJECTIVE: This study evaluated the influence of family meal frequency on the occurrence of common mental disorders (CMD) in children and adolescents over eight months of follow-up. DESIGN: Data from this longitudinal study were derived from the PAAPAS—Parents, Students, Community Health Agents, and Teachers for Healthy Eating—community trial. CMD were evaluated using the General Health Questionnaire. Frequency of family meals (breakfast and dinner) was categorized as “breakfast and dinner regularly with the family”, “at least breakfast or dinner regularly with the family”, and “does not have any meal regularly with the family.” The effect of family meal frequency on CMD was analyzed using generalized estimation equations with log-binomial models for repeated measures. SETTING: This study was conducted in public schools (N = 18) of Duque de Caxias, Rio de Janeiro, Brazil, in 2016. PARTICIPANTS: Children (aged 9–11 years) and adolescents (aged 12–17 years) from the fifth and sixth grades (N = 2,743). RESULTS: These findings suggested that regular family meals were a protective factor for mental health. The adjusted relative risk of CMD was 0.75 (95% confidence interval = 0.69–0.83) for those who had two family meals regularly and 0.87 (95% confidence interval = 0.77–0.97) for those who had only one regular family meal, compared to students who had no regular family meals. CONCLUSIONS: Potential strategies that educate and encourage families about the mental health benefits of eating regular meals together must be explored and implemented.